Natural hazards and internal migration: The role of transient versus permanent shocks - Tanvir Pavel; Syed Hasan; Nafisa Halim; Pallab Mozumder (Global Labor Organization (GLO), 2018)
We analyse internal migration triggered by natural disasters in Bangladesh. We conducted a survey in nine coastal districts and two major cities in Bangladesh to investigate whether floods and cyclones, which can be considered as transient shocks, affect interregional migration differently compared to riverbank erosion that causes loss of lands and thus generates shocks that are permanent in nature. Our findings suggest that transient shocks induce households to move to nearby cities while permanent shocks push people to big cities with more opportunities. Comparing income and expenditure of migrants and non-migrant households, we find that the former group is better-off relative to their counterpart, indicating that welfare can be improved by facilitating migration. Rising exposure to climate change induced natural disasters around the world imply that our findings will be increasingly relevant for designing policies to address vulnerability, particularly for disaster prone countries with weak social safety nets.
Keywords: I38; Q54; Q56; R23; 330; Climate change; Natural disaster; Coastal area; Permanent shock; Transient shocks; Internal migration